Use of reverse angle guide catheter with trans-radial approach in patients undergoing middle meningeal artery embolization - Krothapalli, Neeharika; Fayad, Mohamad; Patel, Smit; Elmashad, Ahmed; Sussman, Eric; Bruno, Charles; Grande, Andrew; Jagadeesan, Bharathi; Killory, Brendan; Alberts, Mark; Kureshi, Inam; Ollenschleger, Martin; et al. (Frontiers in Neurology, 2022)
Background: Trans-radial access (TRA) for MMA embolization has grown due to lower access site complications and greater patient satisfaction. Here, we describe the feasibility of utilizing a 6F Envoy Simmons 2 (6F-SIM2) as a guide catheter with TRA and compare outcomes with trans-femoral approach (TFA) in a single center case series. Methods: We performed a retrospective review of patients who underwent MMA embolization for management of chronic subdural hematoma (cSDH). TRA was performed by utilizing a combination of 6F 90cm Envoy (Codman &Shurtleff, Inc., Rayham, MA) Simmons 2 guide catheter and 5F 125cm Sofia (Microvention, Aliso Viejo, CA) intermediate catheter. Outcomes measured are Modified Rankin Score (mRS) at 90 days, inpatient mortality, post-embolization recurrence, fluoroscopy time and radiation exposure. Results: A total of 71 patients underwent 97 MMA embolization overall with 65 (67%) in trans-femoral access group, 11 (11.3%) in trans-radial access without use of Simmons 2 Guide catheter group and 21 (21.6%) in trans-radial access with use of Simmons 2 Guide catheter group. There were no direct access-related complications in either group. One patient had thromboembolic stroke in trans-femoral group. There was no difference in average procedure-related total fluro time or radiation dose among all three groups. Conclusion: Trans-radial approach using 6F-SIM2 guide catheter coupled with 5F Sofia intermediate catheter is safe and effective. It provides an alternative approach to access distal branches of bilateral anterior circulation in elderly patients with difficult anatomy undergoing MMA embolization.